2012
DOI: 10.1371/journal.pone.0041537
|View full text |Cite
|
Sign up to set email alerts
|

Functional Inactivation of the Genome-Wide Association Study Obesity Gene Neuronal Growth Regulator 1 in Mice Causes a Body Mass Phenotype

Abstract: To date, genome-wide association studies (GWAS) have identified at least 32 novel loci for obesity and body mass-related traits. However, the causal genetic variant and molecular mechanisms of specific susceptibility genes in relation to obesity are yet to be fully confirmed and characterised. Here, we examined whether the candidate gene NEGR1 encoding the neuronal growth regulator 1, also termed neurotractin or Kilon, accounts for the obesity association. To characterise the function of NEGR1 for body weight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
74
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(83 citation statements)
references
References 56 publications
5
74
1
1
Order By: Relevance
“…ENU-induced mutagenesis is a strong method in that it can generate a wide array of subtle phenotypes and the resulting lines may more closely recapitulate the human phenotype compared to engineered knock-out models. Diet challenges are now being employed in this model to identify genetic and environmental interactions in the pathogenesis of metabolic disease (Lee et al 2012; Svenson et al 2008). …”
Section: Mouse Models Of Metabolic Diseasementioning
confidence: 99%
“…ENU-induced mutagenesis is a strong method in that it can generate a wide array of subtle phenotypes and the resulting lines may more closely recapitulate the human phenotype compared to engineered knock-out models. Diet challenges are now being employed in this model to identify genetic and environmental interactions in the pathogenesis of metabolic disease (Lee et al 2012; Svenson et al 2008). …”
Section: Mouse Models Of Metabolic Diseasementioning
confidence: 99%
“…The metabolic rate of the Kilon/NEGR1 KO mouse was lower than that of wild-type mice, but normalising for lean body mass completely removed this effect, implying no impact of the gene on energy expenditure [56] . Although division by lean mass was perhaps not the best way to normalise such data [7,119] , the fact that it removed the apparent impact of the gene on energy expenditure is striking ( fig.…”
Section: Snp Rs2815752mentioning
confidence: 94%
“…Localised expression of Kilon/NEGR1 (and OBCAM), particularly in dendrites, might suggest that these molecules play an important role in rearranging dendritic connectivity of these neurons. Using an in vitro assay with cells derived from mice that had the Kilon/ NEGR1 gene knocked out, it has been shown that Kilon/ NEGR1 plays a key role in both cell-cell adhesion and neurite outgrowth in hypothalamic neurons [56] . AVP and OXT have both been implicated in the regulation of energy balance.…”
Section: Snp Rs2815752mentioning
confidence: 99%
See 2 more Smart Citations